Subsídios para a interpretação de Marília de Dirceu, atribuída a Marcos Portugal - Oliveira, Fabiano Cardoso de (2016)
This work presents a compilation of Marília de Dirceu with the verse to music realization of twelve arias based on the poems of Thomaz Antonio Gonzaga (1744-1807), which authorship is attributed to Portuguese-Brazilian composer Marcos Portugal (1762-1830). This musical elaboration over Gonzaga´s lyres fits better in the modinha musical gender, quite famous and spreaded throughout Brazil and Portugal during the eighteenth and nineteenth century. Its first publication can be found at César das Neves (1841-1920) Cancioneiro de Músicas Populares (Popular Music Songbook) (1893-1899), having versified to music just the first stanza of each collected song, leaving on the interpreter the collocation of the successive stanzas, placed right after the music score and containing all of the known stanzas. Considering that prosodic resolution encompass musicological, interpretative and editorial choices, this study focuses at the presented problem’s and seeks to theoretical subsidies in order to guide the musical interpretation according to the musical and literary text. One of the essential tasks, according the text-based point of view, is to make the interpretation possible through the verses music realization. Keywords: Prosody; Marília de Dirceu; Marcos Portugal; Thomaz Antonio Gonzaga.